2005
DOI: 10.1163/1568561054867837
|View full text |Cite
|
Sign up to set email alerts
|

Modifying stainless steel surfaces with responsive polymers: effect of PS-PAA and PNIPAAM on cell adhesion and oil removal

Abstract: The treatment of stainless steel surfaces with responsive polymers was investigated using X-ray photoelectron spectroscopy and scanning electron microscopy. Poly(N-isopropylacrylamide) (PNIPAAM) is a temperature-sensitive polymer which is soluble in water below 32 • C (Lower Critical Solubility Temperature (LCST)) but collapses and aggregates above 32 • C. This polymer was adsorbed at 50 • C from solutions at different concentrations, followed by rinsing and different drying procedures. Thereby, a large variet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Binding of alpha agglutinin, which is a cell adhesion glycoprotein, to its ligand alpha agglutinin mediates cell-cell contact during mating. Role of electrostatic interaction in adherence was also studied by Park et al [17] and Callewaert et al [18]. They reported that hydrophilic nature of polymers resulted in reduction in yeast cells adhesion, which agreed with our findings in this study.…”
Section: Characterization Of Mdbp As a Biomaterials For Yeast Attachmentsupporting
confidence: 93%
“…Binding of alpha agglutinin, which is a cell adhesion glycoprotein, to its ligand alpha agglutinin mediates cell-cell contact during mating. Role of electrostatic interaction in adherence was also studied by Park et al [17] and Callewaert et al [18]. They reported that hydrophilic nature of polymers resulted in reduction in yeast cells adhesion, which agreed with our findings in this study.…”
Section: Characterization Of Mdbp As a Biomaterials For Yeast Attachmentsupporting
confidence: 93%
“…1,2 A volume phase transition temperature ( VPTT ) of ~33–35 °C makes PNIPAAm hydrogels particularly useful to prepare “smart” materials for biological applications. 36 These applications include microfluidic actuation, 710 separation, 7,11,12 controlled drug delivery 7,1315 and controlled detachment of adsorbed cells and proteins for cell sheet tissue engineering, 7,16,17 anti-fouling coatings, 1820 and “self-cleaning” membranes for implanted biosensors. 2124 …”
Section: Introductionmentioning
confidence: 99%
“…Thermoresponsive poly( N ‐isopropylacrylamide) (PNIPAAm) hydrogels exhibit a reversible volume phase transition from a swollen, hydrophilic state to a deswollen, hydrophobic state when heated above its volume phase transition temperature (VPTT, ≈33–35 °C) . Thus, PNIPAAm hydrogels have been studied for thermally modulated cell‐release applications, including cell sheet tissue engineering, anti‐fouling coatings, and “self‐cleaning membranes” for implanted biosensors . Cell‐release may occur either via a swelling or deswelling‐induced mechanism .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, PNIPAAm hydrogels have been studied for thermally modulated cell‐release applications, including cell sheet tissue engineering, anti‐fouling coatings, and “self‐cleaning membranes” for implanted biosensors . Cell‐release may occur either via a swelling or deswelling‐induced mechanism . For instance, cell sheets cultured at 37 °C ( T > VPTT) were recovered without enzymatic digestion via swelling‐release by lowering the temperature below the VPTT .…”
Section: Introductionmentioning
confidence: 99%